Biochar application in alkaline soil and its effect on soil and plant - Tamer Mohamed SALEM; Khaled Mohamed REFAIE; Abd El-Hamid El-Ghadban Abd El-Lateif SHERIF; Mohamed Ahmed Mohamed EID (Acta Agriculturae Slovenica, 2019)
Scientists reported that biochar can improve soil properties in acidic soils, while in alkaline soils were shown negative results. A field study was done to evaluate the effect of biochar application solely in alkaline soil compared with biochar composts with farm yard manure (BC-FYM) and sulfur (BC-S). The results revealed that using solely biochar decreased yield of potatoes tubers to more than 6 % and 10 % using mineral and organic fertilization, respectively. This was attributed to the alkalinity effect of biochar and raises the soil pH, which might precipitate macro and micro elements in soil and become unavailable for plant absorption. While using mixtures of BC-FYM and BC-S were shown to enhance yield productivity of potatoes tubers 11.7 % and equal to control under mineral fertilization; and 25.13 % and 10.53 % using organic fertilization, respectively. Mixture of BC-FYM and BC-S proved to have the ability for recovering the alkalinity effect of biochar, improve nutrients availability in soil and increase crop yield of potatoes. In general, mixing biochar with FYM was efficient, economical and environmentally sound solution in alkaline soils.